Exploring Relational Transgression and Its Consequences in J.M Coetzee’S Novel Disgrace - Pardi, Pardi; Manugeren, M.; Zein, T. Thyrhaya; Pratiwy, Devi; Asnani, Asnani; Hidayati, Hidayati (Makassar State University, 2024)
Abstract. J.M. Coetzee's Disgrace's relational transgression analysis is essential to comprehending literary analysis, ethical ramifications, society impact, and human behavior. People can learn more about the reasons behind such offenses, as well as the psychological and sociological elements that play a role by analyzing David Lurie's acts and the effects they have.This research aims to analyze the relation transgression committed by the character David Lurie in J.M. Coetzee's novel Disgrace and to delve deeper into why individuals engage in actions that breach social norms and how such actions impact individuals and society. Using a literary psychology approach through a descriptive qualitative research method, this study reveals the dominant characteristics of Lurie that trigger relation transgression. The whole research is conducted by means of descriptive qualitative research method using content analysis. The analysis results show that Lurie has a tendency to violate social norms, particularly concerning his sexual desires. His arrogance and reluctance to apologize exacerbate the situation and isolate him from his social environment. This research contributes to a deeper understanding of the complexity of characters in literary works and the implications of violating relational bonds in individual lives. By referring to the theory of relational transgression, this research highlights how Lurie's actions not only impact himself but also those around him. Effective preventive and intervention techniques may be developed with the help of the examination of Lurie's relational transgression in Disgrace. Communities can be made safer, healthier, and more inclusive by educating people on the underlying causes and effects of such behavior. By understanding the root causes and consequences of relational transgression, it is hoped that more effective prevention and intervention strategies can be developed.Keywords: Apology; arrogance; relation transgression; sexual desire